BIM for railway infrastructure: the case study of the Ogliastro–Sapri High-Speed rail - Biancardo, Salvatore Antonio; Palazzo, Sabrina; Intignano, Mattia; Dell’acqua, Gianluca (International Conference “Environmental Engineering”, 2023)
The Infrastructure-BIM is constantly growing in all the main European countries. The focus of this research is the digital twin creation of the Ogliastro-Sapri High-Speed rail in Italy. The entire project was carried out using Bentley Systems® BIM-based tools such as OpenRail Concept Station and OpenRail Designer. The advantages and limitations of the methodology applied to a real railway project are highlighted. As the main result, a specific interoperable asset manager is proposed for maintenance purposes.